Pengaruh Pendidikan, Jumlah Penduduk, dan Pengangguran Terhadap Kriminalitas di Provinsi Sumatra Barat Periode 2020-2022 - Wulandari, Yupita; Yusnida, Yusnida (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This research aims to analyze the influence of education, population and unemployment on crime in West Sumatra Province in the 2020-2022 period. The data used in this research is secondary data obtained from the Central Statistics Agency (BPS). The analytical method applied is panel data regression with the Common Effect Model, which combines time series and cross-section data processed through the Eviews 12 application program. The results of the research show that education level, population and unemployment rates have a positive and significant effect on crime rates. in West Sumatra Province during the 2020-2022 period.